2022
DOI: 10.3389/fonc.2022.842496
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma, Melanin, and Melanogenesis: The Yin and Yang Relationship

Abstract: Melanin pigment plays a critical role in the protection against the harmful effects of ultraviolet radiation and other environmental stressors. It is produced by the enzymatic transformation of L-tyrosine to dopaquinone and subsequent chemical and biochemical reactions resulting in the formation of various 5,6-dihydroxyindole-2-carboxylic acid (DHICA) and 5,6-dihydroxyindole (DHI) oligomers—main constituents of eumelanin, and benzothiazine and benzothiazole units of pheomelanin. The biosynthesis of melanin is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
140
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(142 citation statements)
references
References 242 publications
(299 reference statements)
1
140
1
Order By: Relevance
“…The reason for such contrasting observations may be the ambivalent role of melanin and melanogenesis in the development of melanoma [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for such contrasting observations may be the ambivalent role of melanin and melanogenesis in the development of melanoma [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Melanogenesis is the most characteristic feature of melanoma 10 . Cellular melanogenesis could affect the regulated cell death of melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the pigmentation score of the high-risk group was visibly higher than those of the low-risk group. In addition, melanogenesis was associated with clinical outcomes of melanoma patients 10 . Brożyna et al 47 indicated that patients with melanotic melanomas have the significantly shorter OS and DFS than those with amelanotic lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations